The Gaming Involvement and Informal Learning Framework. (August 2014) - Iacovides, Ioanna; McAndrew, Patrick; Scanlon, Eileen; Aczel, James
Aim . This article presents amodel of how gaminginvolvement andinformal learning come together in practice. Method . Based on a series of interviews, case studies, and a wider survey, theGaming Involvement and Informal Learning (GIIL) framework indicates how involvement with a variety ofgaming practices can lead to a range of differentlearning experiences . Results . The framework is able to account for bothhow and what people learn from gaming while also highlighting the influence ofplayer identity . Further, theiterative relationship betweenidentity, involvement, andlearning is emphasized: The more strongly someoneidentifies themselves as a gamer, the greater their micro- and macro-levelinvolvement and the more likely they are tolearn from their gaming experiences. Conclusion . Theimplications of the findings are discussed with regard toinformal andformal learning.